Analisis Perubahan Tataguna Lahan Terhadap Usia Bendungan Tilong Di Das Tilong Kabupaten Kupang Propinsi Ntt - Fallo, Yunus; Rispiningtati, Rispiningtati; Harisuseno, Donny (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2013)
The forest degradation rate reached 2,83 million ha every year. From the total forest area of 120,5 million ha, about 59 million ha were critical areas. Besides, the critical Watersheds ini Indonesia increased. The watershed conservation efforts had brought motivation to develop the erosion estimation technologies that could assist in solving the erosion rate estimation problems spatially. The study was carried out at Tilong Watershed, Kupang Regency of NTT Province. The results showed that the value of erosion rate in Tilong Watershed area with existing (year 2010) land utilization condition was 25.428,155 ton/year where the Tilong Watershed total wide was 4.948,75 Ha. Whereas the sediment potential was 7.319,524 ton/year. The Erosion Danger Level was 74,62 %. One of the assumptions why the land erosion rate was very high was because of the misuse of the land in that area. To control the erosion rate, focussed to the recommendation of land utilization direction that referred to The Soil Conservation and Rehabilitation Program (ARLKT) and building of 8 check dam. Meanwhile, the land utilization should notice The RTRW and the cooperation between local inhabitant and the government was needed indeed in the soil conservation and land rehabilitation efforts.Key Words : Erosion, Sediment, Check Dam, GIS